Sosialisasi Pembuatan Teh Daun Kelor di Desa Mertak, Kecamatan Pujut, Kabupaten Lombok Tengah - Nana Mardiana; Lalu rifaldy Fadly; Muhammad Zikrurridho Afwani; Eva Delia Putri Siahaan; Anisa Fitri; Fitrahtul Isnah; Irda Fiqri Immawan; Iyan Radmad Amaliansyah; Khaerul Pahmi; Lalu Wirejunap; Dahlanuddin (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The Moringa plant (Moringa oleifera L) is a plant that grows a lot in various tropical climates, including in Indonesia. Moringa has many benefits and is rich in nutritious substances. One of the villages in Central Lombok where there are many moringa plants is Mertak Village. Moringa plants almost grow in every yard of residents' houses. However, moringa plants are still not widely utilized properly. This is due to a lack of public knowledge about the use of Moringa plants. To overcome this, students of the Mataram University Thematic Community Service Program in Mertak Village conducted socialization on making Moringa leaf tea to provide knowledge about the many benefits of Moringa plants, making products that have economic value to add to the economy of the people of Mertak Village. As a result of this socialization, residents enthusiastically participated and gave a positive response to the taste of Moringa leaf tea